Living under treatment for Systemic Hypertension and Diabetes Mellitus: Feelings and behaviors - Naiara Pinto Alves Pereira; Fernanda Moura Lanza; Selma Maria da Fonseca Viegas
ABSTRACT Objective: To understand the feelings and behaviors of people being treated for Systemic Hypertension (SH) and Diabetes Mellitus (DM). Method: A qualitative study based on Grounded Theory and Symbolic Interactionism, with 27 participants in treatment for SH and DM followed up by the Family Health Strategy team. Open, axial and selective coding was performed, giving rise to three theoretical categories and the central category. Results: The daily life is explicit in the (lack of)care of the self with the chronic disease and feelings of sadness and anxiety are expressed as reasons for the lack of control of the disease. It points out that people take care of themselves because of fear of complications, reinforced the need for guidance on the use of medication and the empowerment of the chronic patient for self-care and care for the other. Final considerations: Knowing behaviors and feelings of people with SH and/or DM allows a professional performance beyond the chronic condition.